Vision-Related Quality of Life among Patients with Different Types of Age-Related Macular Degeneration - Abdin, Alaa Din; Eppinger, Anna; Aljundi, Wissam; Abu-Dail, Yaser; Munteanu, Cristian; Weinstein, Isabel; Seitz, Berthold (Klinische Monatsblätter für Augenheilkunde, 2023)
Background This study aimed to assess the vision-related quality of life (VRQol) of patients with age-related macular degeneration (AMD) and to evaluate VRQol according to different types of AMD.Methods In this small-scale, single-center, prospective investigation, patients with AMD and subjects without any signs of macular disease were asked to complete the NEI-VFQ-39. A total of 159 subjects were included and grouped according to the type of AMD as follows: 40 patients with dry AMD in both eyes (DD), 40 patients with exudative AMD in one eye (DE), 41 patients with exudative AMD in both eyes (EE), and 38 subjects without any signs of macular disease, as a control group (CG).Results The average age of the participants was 76 ± 7 years, and 44% were male. Most participants were retired (22.4%), and 75% of patients were initially diagnosed by their ophthalmologist. All the AMD groups had significantly worse overall VRQol than the CG. For general vision, near vision, mental health, and role difficulties, all the AMD groups had significantly lower scores than the CG. For distance vision, color vision, peripheral vision, driving difficulties, dependency, and social functioning, only patients in the EE and DE groups had significantly worse scores than the CG. The type of retinal fluid in patients with exudative AMD had no effect on overall VRQol; however, we found that the presence of pigment epithelial detachment could be associated with more role difficulties, such as completing work or working long hours.Conclusion All types of AMD had a negative effect on vision-related quality of life. This effect was significantly more pronounced in patients with exudative AMD in at least one eye. However, the type of retinal fluid in patients with exudative AMD had no influence on their overall vision-related quality of life.
Keywords: NEI-VFQ-39; retinal fluid; age-related macular degeneration; quality of life